Scientific Mapping of Research Evolution on Buddhist Philosophy: A Bibliometric Analysis - Pal, Suman; Kumar, Vinod (Journal of Data Science, Informetrics, and Citation Studies)
Buddhist philosophy is an important and distinct part of the Indian knowledge tradition. Buddhist philosophy presents its strong signature at the global level due to its medium path and public welfare concerns. The international reach of Buddhist philosophy as an important part of the Indian knowledge system, the kind and how strong the connection of important keywords related to Buddhist philosophy is with various dimensions of various global knowledge disciplines, the analysis of the most productive country, researcher and sources (journal) in the context of Buddhist philosophy is the main concern of this study. In this study, a total of 690 publications related to Buddhist philosophy available on the Scopus database from 1985 to 2024 (09/09/2024 at 16:00 hr) have been bibliometric analyzed with the help of VOSViewer software (version 1.6.20 edition). The results of the study show that the 1st publication of Buddhist philosophy on the Scopus database was in the year 1985 and the maximum (69) publications have been published in the year 2023. United States America is the top country with a total of 240 (about 35%) publications, which has received the maximum (total of 2189) citations. The UK ranks 2nd with 59 publications and 391 citations and India secured 6th rank with 34 publications and 247 citations. The most famous and trending keywords are 'Buddhism' and 'Buddhist philosophy'. The most productive researchers and journals related to Buddhist philosophy are Garfield, J. L. (15 publications and 105 citations in total) and Journal of Indian Philosophy (26 publications and 55 citations) respectively.
Keywords: Bibliometric analysis; Buddhist Philosophy; Density Visualization Mapping; Indian Knowledge System; Network Visualization and VOS viewer Software.